Stories of martial law teaching and learning processes between activist mothers and their children - Cupino, Fleur De Lys T. Castelo (College of Education, University of the Philippines Diliman, 2015)
"A study on how teaching-learning processes, informed by the learning theories of social and dialectical constructivism, epistemological beliefs, emotion in learning, critical theory of knowledge and developmental phases in learning affected national democratic Martial Law activist mothers and their children as they transformed selves, each other and the environment, taking into account the community, norms and mediating instruments as well as culture, politics, economics, history and education, as espoused by the cultural-historical activity theory, and using constructivist grounded theory and feminist research methodologies. Results show that social practice as manifested in the cultural-historical milieu and social interactions within the immediate environment were central to learning and shaping the individual's consciousness, leading to a process of becoming and to transformation of self, others and the environment, as mothers taught and children learned about the values of rights, freedom, social reality, selflessness, responsibility, simple living and determination through storytelling, exposure and teaching by example. The fathers assumed a lesser role in educating on activism and Martial Law, friends of mothers complemented the mothers' stories while grandparents implicitly contested those stories. The epistemological beliefs articulated were: a) learning is complex and process-oriented; b) learning requires critical thinking; c) knowledge is a product of social experience; d) class consciousness affects knowledge; e) learning leads to transformation; and f) learning is a continuous process while specific resource persons identified religious epistemologies and maternal thinking as sources of beliefs on knowledge and knowing. The teaching of Martial Law in history class needs to be more dynamic, rigorous and must reflect reality. This research contributes to educational psychology, feminist historiography, the teaching of history, curriculum studies, and the use of constructivist grounded theory and feminist methodologies in educational research."